Alteration of complement hemolytic activity in different trauma and sepsis models - Ehrnthaller, Christian; Amara, Umme; Weckbach, Sebastian; Kalbitz, Miriam; Huber-Lang, Markus; Bahrami, Soheyl (Journal of Inflammation Research, 2012)
Complement activation is involved in various diseases in which innate immunity plays a crucial role. However, its pathophysiological relevance is not clearly understood. Experimental models have been widely used to characterize the role of complement activation under different pathological conditions, such as hypoxemia, ischemia and reperfusion, tissue damage, and polymicrobial invasion. Screening of the complement status and function is, however, strongly dependent on the laboratory-specific techniques being used to sample and measure complement, making it difficult to compare the results found in different laboratories. Therefore, we evaluated complement function by measuring complement hemolytic activity (CH50) in various animal models of isolated ischemia reperfusion (I/R: kidney, liver, gut), hemorrhagic traumatic shock (HTS), endotoxic shock (LPS), and sepsis (CLP). Complement activation was less pronounced in isolated models of ischemia and reperfusion, whereas a strong complement response was observed early after HTS, CLP, and LPS. In summary, CH50 is a well-established, quick, and cost-effective screening method of complement function. However, because we obtained different results in clinically relevant animal models, further differentiation using specific complement factor analysis is necessary. © 2012 Charchaflieh et al, publisher and licensee Dove Medical Press Ltd.
CRIS-Team Scopus Importer:2020-12-21
Keywords: CH50; Complement; Hemorrhagic shock; Inflammation; Ischemia/reperfusion; Sepsis